Ready-mix concrete or mortar, or precast concrete composition, comprising ground granulated blast furnace slag, an alkali sulfate activator, and a PCE-type water-reducing polymer
A GGBS-based concrete composition with a tailored water-reducing polymer and alkali sulfate activator maintains fluidity and strength, addressing the limitations of conventional polymers in low-carbon binders, achieving performance comparable to OPC.
Patent Information
- Application Number
- JP2024544795
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-27
- Filing Date
- 2023-01-27
- Publication Date
- 2025-01-24
AI Technical Summary
Existing concrete and mortar compositions using low-carbon binders like GGBS face issues with initial liquidity and open time due to the presence of alkaline sulfates, leading to reduced fluidity and mechanical strength, which conventional water-reducing polymers like PCE fail to address effectively.
A composition incorporating ground blast furnace slag powder (GGBS) with a specific water-reducing polymer containing monomer units A, B, C, and D, along with an alkali sulfate activator, maintains slump flow classes S3, S4, or S5 for at least 2 hours, enhancing initial strength and fluidity.
The solution ensures stable fluidity and mechanical strength comparable to 100% OPC compositions, maintaining slump flow and initial strength without adverse effects on mechanical properties over time.
Smart Images

Figure 2025502538000001_ABST
Abstract
Description
[Technical field]
[0001] The technical field of the invention relates to ready-mix concrete or mortar compositions or precast concrete compositions comprising at least one alkali sulfate which provides an acceleration effect and at least one water-reducing polymer fluidizing effect.
[0002] More particularly, the present invention relates to a low carbon binder comprising ground granulated blast furnace slag (GGBS) activated with an alkali sulfate activator for ready-mix concrete or mortar containing a water-reducing polymer or for precast concrete compositions. [Background technology]
[0003] Supplementary cementitious materials (SCMs), such as mortars and concretes, containing significant amounts of ground granulated blast furnace slag (GGBS) are increasingly being used because ordinary Portland cement production has a strong negative impact on the environment due to the large amount of carbon dioxide emissions. The production of cement essentially generates CO2 through the decarbonation of limestone (Equation (1)) during the calcination of the raw materials at very high temperatures (1450°C) in the kiln. CaCO3(s) → CaO(s) + CO2(g) (Formula (1))
[0004] Additionally, carbon dioxide is released as a result of the combustion of fossil fuels required to heat the cement kilns. Adding in the additional emissions from grinding, we get almost one tonne of CO2 per tonne of Portland cement. Overall, the cement industry is responsible for around 7-9% of global carbon dioxide emissions.
[0005] Furthermore, in order to produce mortar or concrete with the desired early stage mechanical properties, it is generally necessary to add accelerators to binders containing significant amounts of SCM. To accelerate the strength development of these alternative binders, activators are often used. Activators are compounds that induce alkaline conditions favorable for the strength development of SCM-containing binders. Activators are compounds that have sodium or potassium as their cations and most commonly have hydroxides, silicates, sulfates, thiocyanates or carbonates as their anions. Low carbon alkali-activated binders, including GGBS and other SCMs such as metakaolin, clays (calcined or uncalcined), pozzolanic materials, exhibit rheological problems in terms of early flow and open time that do not correspond to the rheology required to have good workability for a sufficient period of time. This is mainly due to the addition of alkali activation and the presence of highly soluble sulfates in the solution after the addition of water.
[0006] Examples of alkaline activation are salts such as sodium sulfate. Some anhydrites, especially the highly soluble anhydrites, can lead to high and rapid presence of soluble sulfates in the polar solution, which can cause the same rheological problems as in the presence of alkaline salts. These anhydrites (mainly thermal anhydrites) are characterized by high conductivity, high pH and high zeta potential.
[0007] Nevertheless, the addition of alkali and soluble sulfates allows one to boost early strength and achieve compressive strength values for low carbon binder based compositions that are comparable to 100% OPC compositions.
[0008] Water-reducing polymers are used to increase the fluidity of concrete taking into account the desired consistency class defined in the standard NF EN 206. Common water-reducing agents, also called superplasticizers / superplasticizers, such as lignin sulfonate polymers, melamine sulfonate polymers, naphthalene sulfonate polymers, polycarboxylic acid ether polymers (PCE), polyoxyethylene phosphonates, phosphates, vinyl copolymers, are less effective when an alkali sulfate activator is added to the composition.
[0009] Generally, the water-reducing polymers are not able to perform their role and the concrete or mortar is not as fluid or practical as expected, because the alkali sulfates generally reduce the polymer dissolution by reducing its efficiency.
[0010] WO 2021 / 204384 A1 discloses a performance enhancing additive consisting of at least one alkaline activator containing a kosmotropic ion, at least one water-reducing polymer and at least one salt containing a chaotropic ion, which promotes the hydration of binders and increases their fluidity. The chaotropic ion makes it possible to manage the fluidity of the system and its open time after the addition of the alkaline activator (cosmotropic ion).
[0011] The addition of chaotropic ions is indeed a very effective solution to the problem of inactivation of common water reducers caused by soluble / solubilized sulfates in concretes and mortars containing alkali-activated low-carbon binders. Nevertheless, this solution is difficult to implement in the field since it requires some changes in the normal process procedures. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] International Publication No. 2021 / 204384 Summary of the Invention [Problem to be solved by the invention]
[0013] It would therefore be beneficial to have a different solution to the above, which could be suitable for any kind of alternative binder composition made with SCM and activator.
[0014] In this regard, the present invention aims to address at least one of the above problems and / or needs by achieving at least one of the following objectives:
[0015] -O1- Providing a ready-mix concrete or mortar composition or a precast concrete composition comprising an alternative binder composition made with SCM and activated with an activator and fluidized with at least one common water-reducing polymer.
[0016] To provide a ready-mix concrete or mortar composition or a precast concrete composition containing GGBS and having low carbon, which has suitable rheology in a wet state before hardening and good mechanical properties, particularly good early strength, after hardening.
[0017] -O3- To provide an efficient method for fluidizing a wet GGBS-containing and low carbon concrete or industrial mortar composition before hardening and accelerating strength development after hardening, said composition comprising at least one alkaline sulfate accelerator.
[0018] -O4- To provide a method for fluidifying a binder composition comprising GGBS and optionally other supplemental cementitious materials and / or filler materials, and for fluidifying wet mortar and concrete. [Means for solving the problem]
[0019] In a first aspect, the present invention relates to a wet ready-mix concrete or mortar composition, in particular for building and civil engineering works, or a wet precast concrete composition, comprising at least one aggregate (A), a binder composition (B), at least one alkali and / or alkaline earth sulfate activator (C), water (D) and at least one water-reducing polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The wet ready-mix concrete or mortar composition or wet precast concrete composition is classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, and The water-reducible polymer (E) comprises the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers in the range of 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N, or S. is a copolymer comprising It relates to a wet ready-mix concrete or mortar composition or a wet precast concrete composition.
[0020] In a second aspect, the present invention relates to a method for preparing a wet concrete composition or a wet mortar composition classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, comprising the steps of: - at least one aggregate (A), - a binder composition (B), at least one alkaline sulfate activator (C), - Water (D), and - at least one water-reducing polymer (E); into a mixing chamber, The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The water-reducible polymer (E) is composed of the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising wherein said wet concrete or wet industrial mortar composition remains classified in the same slump flow class for at least 2 hours after introducing all the above amounts of A, B, C, D and E in the mixing chamber.
[0021] In a third aspect, the present invention relates to a method for maintaining a wet concrete composition or a wet industrial mortar composition in a single slump flow class according to standard NF EN 206 for at least 2 hours, said composition comprising at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D) and at least one water-reducing polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The water-reducible polymer (E) comprises the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising A period of at least 2 hours begins after all of the above amounts of A, B, C, D and E have been introduced into the mixing chamber, and The method relates to a process in which the single slump flow class is S3, S4, or S5.
[0022] In a fourth aspect, the present invention provides a method for imparting to a hardened low carbon GGBS containing binder-based concrete or mortar composition early age compressive strength values comparable to those of a hardened 100% OPC binder-based concrete or mortar composition, comprising the steps of: A wet precursor P1 of a low-carbon GGBS-containing binder-based concrete or mortar composition comprises at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D), and at least one water-reducible polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The wet precursor P1 is classified into one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, and said wet precursor P1 remains in the same slump flow class for at least 2 hours after introducing all the above amounts of components A, B, C, D, and E into the mixing chamber; a wet precursor P2 of a 100% OPC binder based concrete or mortar composition contains the same components (A), (D), (E) as P1, (A), 100% OPC, (D), and (E) in the same concentrations as (A), (B), (D), and (E) in P1, and the ratio C / 100% OPC binder is the same as the C / B ratio in P1; The method comprises the steps of: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [where: [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. The water-reducing polymer (E) is a copolymer comprising: It concerns the method.
[0023] General definition In accordance with the terminology herein, the following non-limiting definitions must be taken into account:
[0024] "Binder" refers to a material comprised of one or more hydraulic binders and optionally one or more supplemental cementitious materials and optionally one or more filler materials.
[0025] "Hydraulic binder" refers to a material that hardens by reacting with water. Here, the term refers to pure ordinary Portland cement, and standardized cements made with calcium aluminate cement, calcium sulfoaluminate cement, belite cement, ground granulated blast furnace slag, converter slag, ladle slag, supersulfated cement, hydraulic lime, cement kiln dust, or mixtures thereof.
[0026] "Supplementary cementitious material" refers to a material that contributes to the strength of the binder due to latent hydraulic or pozzolanic activity, where the term refers to ground granulated blast furnace slag, fly ash, activated clay, silica fume, converter slag, natural pozzolanic materials, rice husk ash, activated recycled concrete fine aggregate, or mixtures thereof.
[0027] "Filler material" refers to a material whose primary role in the binder is physical rather than chemical. Fillers occupy pore space and are less energy intensive and are used as a substitute for hydraulic binders and auxiliary cementitious materials. Here, the term refers to crushed limestone, crushed dolomite, marble dust, silica sand, recycled concrete fine aggregate, or mixtures thereof.
[0028] "Slag" refers to the lithic waste material separated from metals during the smelting or refining of ores.
[0029] "GGBS" or "GGBFS": Ground granulated blast furnace slag, which is equivalent to blast furnace slag, granulated blast furnace slag (GBFS), granulated blast furnace slag powder, and blast furnace slag fine aggregate.
[0030] "Cement" is understood to mean a powdered material made for use in making mortar or concrete. It is a mineral binder, possibly free of any organic compounds, including ordinary Portland cement, Portland slag cement, Portland silica fume cement, Portland pozzolana cement, Portland fly ash cement, Portland burnt shale cement, Portland limestone cement, Portland composite cement, blast furnace slag cement, supersulphated cement, calcium aluminate cement, pozzolanic cement and composite cement.
[0031] "Mortar" refers to a material composed of a binder and an aggregate, such as sand.
[0032] "Concrete" refers to a material composed of a binder and aggregate, such as sand or (fine) gravel.
[0033] "Dry weight" is the weight of a material in its natural state (without the addition of exogenous water or other solutions).
[0034] "Apparent viscosity" is the quotient of the applied shear stress to a fluid divided by the shear rate and is used to express the shear rate-dependent viscosity of non-Newtonian fluids in the International System of Units (IS), and is expressed in pascal seconds (Pa s).
[0035] "CEM X" denotes a class of cement according to standards EN 197-1 and EN 197-5.
[0036] "Open time" is the length of time that mortar or concrete can be processed.
[0037] "Early strength" corresponds to the mechanical strength of a mortar or concrete after the first 24 hours after mixing all of its components.
[0038] "Comparable" means that the two values differ by at most 10%.
[0039] "Soluble" when referring to a sulfate or anhydrite means that when said sulfate or anhydrite is solubilized in water at a concentration of 10 g / L, the resulting solution has a pH of at least 10.
[0040] The "poral solution" corresponds to the interstitial liquid phase inside the pores. [Brief description of the drawings]
[0041] [Figure 1] FIG. 1 is a bar graph showing compressive strength as a function of time. [Diagram 2] Figure 2 is a graph reporting the Abrams cone of two CEM III / B concretes with admixtures of 1.5% Na2SO4 and 1.6% Tempo 12 (conventional PCE, black) or 0.5% Marla RB 1050. Figure 2 shows the results of rheological measurements performed by Abrams cone for precast applications. The room temperature was higher than standard laboratory conditions (25-26°C) to simulate deteriorated conditions for precast applications. [Diagram 3] FIG. 3 is a bar graph showing compressive strength as a function of time. [Figure 4] FIG. 4 is a graph showing the spreading in an Abrams mini-cone for CEM III / B based MBE with 1.5% Na2SO4 addition and aided by different superplasticizer combinations. [Diagram 5] FIG. 5 is a graph showing the spreading in an Abrams mini-cone for CEM III / B based MBE with 1.5% Na2SO4 addition and aided by different superplasticizer combinations. [Figure 6] FIG. 6 is a graph depicting measured stress versus shear rate for HPEG PCE in the presence of sodium sulfate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0042] Ready-mix concrete or mortar or precast concrete composition The wet ready-mix concrete or mortar composition, or wet precast concrete composition, particularly for building and civil engineering construction, comprises at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D), and at least one water-reducing polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The wet ready-mix concrete or mortar composition or the wet precast concrete composition is classified into one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, The water-reducible polymer (E) may be composed of the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. It is a copolymer comprising:
[0043] Advantageously, the wet ready-mix concrete or mortar compositions remain in the same slump flow class for at least 2 hours after the addition of various amounts of water (D).
[0044] Aggregate (A) Aggregates include a large class of particulate materials used in construction, including sand, gravel, crushed stone, slag (uncrushed), recycled concrete, and geosynthetic aggregates. They serve as reinforcing agents that impart strength to the overall composite material.
[0045] In addition to the aggregates mentioned above, the ready-mix composition may also contain fillers, such as fillers based on quartz, limestone, or clay, and mixtures thereof, as well as lightweight fillers such as perlite, diatomaceous earth, expanded mica (vermiculite), and foamed sand, and mixtures thereof.
[0046] The total content of these fillers is preferably within the range of 0.1% by mass to 10% by mass of the total mass of the aggregate (A).
[0047] Binder Composition (B) According to the invention, the binder composition (B) comprises (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Includes.
[0048] The binder composition (B) can be made of 100% GGBS (b1). In some embodiments, the binder composition (B) also comprises at least one hydraulic binder (b2) other than GGBS according to standards EN 197-1 and EN 197-5. In these embodiments, the content of b2 is comprised in the range of 0.1% to 60% by weight of the total weight of the binder composition (B), preferably 3% to 55% by weight of the total weight of the binder composition (B), more preferably 5% to 50% by weight of the total weight of the binder composition (B).
[0049] In some embodiments, the ready-mix concrete or mortar, or precast concrete composition according to the invention comprises an auxiliary cementitious material (b3). Advantageously, b3 is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, or mixtures thereof. In these embodiments, the content of b3 is comprised in the range of 0.1% to 90% by weight of the total weight of the binder composition (B), preferably 5% to 80% by weight of the total weight of the binder composition (B), more preferably 10% to 70% by weight of the total weight of the binder composition (B).
[0050] In some embodiments, the ready-mix concrete or mortar, or precast concrete composition according to the invention comprises one or more filler materials (b4). Advantageously, b4 is selected from the group consisting of crushed limestone, crushed dolomite, marble powder, silica sand, recycled fine concrete aggregate, or mixtures thereof. In these embodiments, the content of b4 is comprised in the range of 0.1% to 60% by weight of the total weight of the binder composition (B), preferably 3% to 55% by weight of the total weight of the binder composition (B), more preferably 5% to 50% by weight of the total weight of the binder composition (B).
[0051] In some embodiments, the ready-mix concrete or mortar, or precast concrete composition according to the invention comprises at least one hydraulic binder other than GGBS (b2) and / or auxiliary cementitious material (b3) and / or one or more filler materials (b4) according to standards EN 197-1 and EN 197-5. In other words, the binder composition (B) can be a mixture of GGBS (b1), at least one hydraulic binder other than GGBS (b2) and auxiliary cementitious material (b3) according to standards EN 197-1 and EN 197-5, or a mixture of GGBS (b1), at least one hydraulic binder other than GGBS (b2) and one or more filler materials (b4) according to standards EN 197-1 and EN 197-5, or a mixture of GGBS (b1), auxiliary cementitious material (b3) and one or more filler materials (b4), or a mixture of GGBS (b1), at least one hydraulic binder other than GGBS (b2), auxiliary cementitious material (b3) and one or more filler materials (b4) according to standards EN 197-1 and EN 197-5. In these embodiments, the total content of b1 is in the range of 20% by mass to 95% by mass of the total mass of binder composition (B), preferably 30% by mass to 90% by mass of the total mass of binder composition (B), and more preferably 50% by mass to 80% by mass of the total mass of binder composition (B).
[0052] In some embodiments, the binder composition (B) is advantageously enriched with one or several other components, preferably materials selected from the following list, in particular functional additives selected from the following:
[0053] <Water retention agent> Water retention agents have the ability to hold the mixing water before hardening. The water is then trapped in the wet paste formulation improving bonding. To some extent, the water is less absorbed by the substrate.
[0054] The water retention agent is preferably selected from the group comprising modified cellulose, modified guar, modified cellulose ethers and / or guar ethers and mixtures thereof, more preferably from the group consisting of methylcellulose, methylhydroxypropylcellulose, methylhydroxyethyl-cellulose and mixtures thereof.
[0055] <Rheology modifier> Possible rheology modifiers (also called "thickeners") are preferably selected from the group comprising, more preferably consisting of, clays, starch ethers, cellulose ethers and / or gums (e.g. welan gum xanthan, diutan gum, succinoglycan), modified polysaccharides, preferably modified starch ethers, polyvinyl alcohols, polyacrylamides, clays, sepiolite, bentonite and mixtures thereof, more preferably selected from the group of clays, bentonite, montmorillonite.
[0056] <Antifoam agent / Anti-foam> The applicable antifoaming agents are preferably selected in the group comprising, more preferably consisting of, polyether polyols, diphenyl oxide sulfonates, acetylenic diols, amines, and mixtures thereof.
[0057] <Biocides> The applicable biocides are preferably selected in the group comprising, more preferably consisting of, mineral oxides such as zinc oxide and mixtures thereof.
[0058] <Pigments> The applicable pigments are preferably selected in the group comprising, more preferably consisting of, TiO2, iron oxides, and mixtures thereof.
[0059] <Flame retardants> Possible flame retardants (or flame retardants) that allow for an increase in the fire resistance of the composition and / or a decrease in the rate of fire spread are preferably selected from the group that includes, and more preferably consists of, the following: Minerals, preferably aluminum hydroxide [Al(OH)3, ATH], magnesium hydroxide MDH, hydromagnesite, hydrates, red phosphorus, and boron compounds, preferably borates; Organohalogen compounds, preferably organochlorines, more preferably, for example, chlorendic acid derivatives and chlorinated paraffins; organobromine compounds, for example, decaBDE, decaBDE, decaBDE, polymeric brominated compounds, preferably brominated polystyrene, brominated carbonate oligomers (BCO), brominated epoxy oligomers (BEO), tetrabromophthalic anhydride, tetrabromobisphenol A (TBBPA), and hexabromocyclododecane (HBCD); Antimony, preferably sodium pentoxide and sodium antimonite, Organophosphorus compounds, preferably organophosphates, TPP, RDP, BPADP, tri-o-cresyl phosphate, phosphonates, preferably DMMP and phosphinates, · Chlorophosphates such as TMCP and TDCP.
[0060] <Air entraining agent> The air entraining agents (surfactants) are advantageously selected from the group comprising, more preferably consisting of, natural resins, sulfated or sulfonated compounds, synthetic detergents, organic fatty acids, betaines and mixtures thereof, preferably from the group comprising, more preferably consisting of, lignin sulfonates, basic soaps of fatty acids and mixtures thereof, more preferably from the group comprising, more preferably consisting of, sulfonated olefins, sodium lauryl sulfate and mixtures thereof, more preferably from the group comprising, more preferably consisting of, sulfonated olefins, sodium lauryl sulfate and mixtures thereof.
[0061] <Retarder> The retarding agent is advantageously selected from the group comprising, and more preferably consisting of, tartaric acid and its salts: sodium or potassium salts, citric acid and its salts: sodium (trisodium citrate), sodium gluconate, sodium glucoheptonate, tartrates and mixtures thereof. Textiles · Dispersion powder Wetting agent Polymer resin Complexing agents Polyol-based drying shrinkage reducing agents.
[0062] The total content of these optional other components is preferably comprised within the range of 0.001% to 10% by weight of the total weight of the binder fraction.
[0063] Alkaline sulfate activator (C) Generally, the alkali sulfate activator (C) is in the form of a salt with countercation sodium, potassium or lithium, but there are some anhydrites, especially very soluble anhydrites, which can lead to a high and fast presence of soluble sulfates in polar solutions, causing the same rheological problems as in the presence of alkali sulfates. These anhydrites (mainly thermal anhydrites) are characterized by high conductivity, high pH and high zeta potential. In the sense of the present invention, the alkali sulfate activator (C) includes anhydrites that lead to a pH of at least 10 when solubilized in water at a concentration of 10 g / L.
[0064] Generally, in the wet ready-mix concrete or mortar composition or wet precast concrete composition according to the invention, the mass ratio C / B of said alkali sulfate activator (C) to the binder composition (B) is within the range of 0.001 to 0.15.
[0065] Water (D) Advantageously, the mass ratio of water to hydraulic binder composition (D / B) is comprised between 0.08 and 1.0, preferably between 0.25 and 0.9, more preferably selected in the group comprising the following ranges, advantageously consisting only of the following ranges: [0.25; 0.35[; [0.35; 0.45[; [0.45; 0.6[; [0.6; 0.9].
[0066] Water-reducing polymer (E) According to the invention, the water-reducible polymer (E) is a copolymer comprising the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0-40 mol %; The amount of monomer unit B is 25-95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m-R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, straight or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S.
[0067] In an embodiment, the sum of the amount of monomeric unit A, the amount of monomeric unit B, the amount of monomeric unit C, and the amount of monomeric unit D is 100 mole %.
[0068] In another embodiment, the water-reducible polymer (E) comprises at least another monomer unit in an amount of up to 20 mol %, preferably resulting from the polymerization of any unsaturated monomer capable of copolymerizing with any of the monomers contained in the PCE, with the proviso that the resulting polymer cannot be ViscoCrete® Tempo 12 manufactured by Sika®.
[0069] Preferably, the amount of monomer unit A is from 5 to 35 mol %, more preferably from 10 to 30 mol %, and even more preferably from 15 to 25 mol %.
[0070] Preferably, the amount of monomer unit B is from 25 to 95 mol %, more preferably from 35 to 80 mol %, and even more preferably from 45 to 65 mol %.
[0071] Preferably, the amount of monomer unit C is from 5 to 50 mol %, more preferably from 15 to 40 mol %, and even more preferably from 20 to 30 mol %.
[0072] Preferably, the amount of monomer unit D is from 0 to 25 mol %, more preferably from 5 to 20 mol %, even more preferably from 10 to 15 mol %.
[0073] In embodiments in which the water-reducible polymer (E) contains phosphate functional groups, at least a portion of the constitutional units derived from carboxylic acid monomers are substituted with phosphate.
[0074] In embodiments in which the water-reducible polymer (E) contains phosphonate functional groups, at least a portion of the constitutional units derived from carboxylic acid monomers are substituted with phosphonate.
[0075] Preferably, the water-reducible polymer is anionic, cationic, or zwitterionic.
[0076] Preferably, the water-reducible polymer has a molecular weight of 5000 g·mol -1 ~300000 g mol -1 The molecular weight is determined by the mass of the compound.
[0077] The content of the water-reducing polymer is preferably from 0.05 to 3% by mass of the binder composition (B).
[0078] In an embodiment, the water-reducible polymer (E) is HPEG, which is a copolymer derived from (meth)acrylic acid, itaconic acid monomers, ω-hydroxy-α-methallyl poly(ethylene glycol) macromonomers, or ω-methoxy-α-methallyl poly(ethylene glycol).
[0079] In this embodiment, the water-reducible polymer (E) is a copolymer comprising the following monomer units: - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 is hydrogen or methyl; R2 is hydrogen; Z1 is methyl; Z2 is a bond; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, straight or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S.
[0080] In this embodiment, the amount of monomer units B is preferably 25 to 95 mol%, more preferably 35 to 80 mol%, even more preferably 45 to 65 mol%, the amount of monomer units C is 5 to 50 mol%, more preferably 15 to 40 mol%, even more preferably 20 to 30 mol%, and the amount of monomer units D is 1 to 25 mol%, more preferably 5 to 20 mol%, even more preferably 10 to 15 mol%.
[0081] In another embodiment, the water-reducible polymer (E) is APEG, which is a block copolymer of the ABAB type, where the A units are derived from maleic acid monomers and the B units are derived from ω-hydroxy-α-allyl poly(ethylene glycol) macromonomers.
[0082] In this embodiment, the water-reducible polymer (E) is a copolymer comprising the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 is hydrogen or methyl; R2 is hydrogen; Z1 is methyl; Z2 is a bond; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, straight or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S.
[0083] In this embodiment, the amount of monomer units A is preferably 5 to 35 mol%, more preferably 10 to 30 mol%, even more preferably 15 to 25 mol%, the amount of monomer units B is preferably 25 to 95 mol%, more preferably 35 to 80 mol%, even more preferably 45 to 65 mol%, the amount of monomer units C is preferably 5 to 50 mol%, more preferably 15 to 40 mol%, even more preferably 20 to 30 mol%, and the amount of monomer units D is preferably 1 to 25 mol%, more preferably 5 to 20 mol%, even more preferably 10 to 15 mol%.
[0084] In another embodiment, the water-reducible polymer (E) is VPEG. VPEG is a vinyl ether-based PCE.
[0085] In this embodiment, the water-reducible polymer (E) is a copolymer comprising the following monomer units: - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 is hydrogen or methyl; R2 is hydrogen; Z1 is a bond; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, straight or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S.
[0086] In this embodiment, preferably, the amount of monomer units B is 25 to 95 mol%, more preferably 35 to 80 mol%, even more preferably 45 to 65 mol%, the amount of monomer units C is 5 to 50 mol%, more preferably 15 to 40 mol%, even more preferably 20 to 30 mol%, and the amount of monomer units D is 1 to 25 mol%, more preferably 5 to 20 mol%, even more preferably 10 to 15 mol%.
[0087] In another embodiment, the water-reducible polymer (E) is an IPEG, which is a copolymer derived from acrylic acid monomers and isoprenol poly(ethylene glycol) macromonomers.
[0088] In this embodiment, the water-reducible polymer (E) is a copolymer comprising the following monomer units: - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 is hydrogen or methyl; R2 is hydrogen; Z1 is ethyl; Z2 is a bond; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O)n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, straight or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S.
[0089] In this embodiment, preferably, the amount of monomer units B is 25 to 95 mol%, more preferably 35 to 80 mol%, even more preferably 45 to 65 mol%, the amount of monomer units C is 5 to 50 mol%, more preferably 15 to 40 mol%, even more preferably 20 to 30 mol%, and the amount of monomer units D is 1 to 25 mol%, more preferably 5 to 20 mol%, even more preferably 10 to 15 mol%.
[0090] Method for preparing a wet concrete or wet mortar composition The present invention relates to a method for preparing a wet concrete or wet mortar composition classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, which comprises the steps of: at least one aggregate (A); Binder composition (B), at least one alkaline sulfate activator (C); Water (D), and At least one water-reducible polymer (E) into a mixing chamber, The binder composition (B) (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The water-reducible polymer (E) is composed of the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n-R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising wherein said wet concrete or wet industrial mortar composition remains classified in the same slump flow class for at least 2 hours after introducing all of the above amounts of A, B, C, D and E into the mixing chamber.
[0091] The components of the wet concrete or wet mortar compositions obtained by the method according to the invention and classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206 have the same characteristics apart from those described in the above section "Ready-mixed concrete or mortar, or precast concrete compositions".
[0092] In particular, in the process according to the invention, the water-reducible polymer (E) is anionic, cationic or zwitterionic.
[0093] In particular, in the method according to the invention, the mass ratio C / B of said alkali sulfate activator (C) to the binder composition (B) is comprised between 0.001 and 0.15.
[0094] In particular, in the method according to the invention, the auxiliary cementitious material (b3) is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, or mixtures thereof, and / or the filler material (b4) is selected from the group consisting of crushed limestone, crushed dolomite, marble flour, silica sand, recycled concrete fine aggregate, or mixtures thereof.
[0095] A method for maintaining wet concrete or wet industrial mortar compositions at a single slump flow class measured according to EN 12350-2 for at least 2 hours as described in standard NF EN 206 The present invention relates to a method for maintaining a wet concrete or wet industrial mortar composition in a single slump flow class according to standard NF EN 206 for at least 2 hours, said composition comprising at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D) and at least one water-reducing polymer (E), wherein the binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS), (b2) optionally, at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) Optionally, one or more filler materials Including, The water-reducible polymer (E) is composed of the following monomer units: - Unit A [ka] - Unit B [ka] - Unit C [ka] - Unit D [ka] [In the formula, [ka] represents the binding site of the monomer unit, The amount of monomer unit A is 0 to 40 mol %; The amount of monomer unit B is 25 to 95 mol %; The amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R1 and R2 are independently hydrogen or methyl; Z1 is a bond, methyl, or ethyl; Z2 is a bond, -CH2CH2O-, -CH2CH2OCH2CH2O-, or -CH2CH2CH2CH2O-; R3 is -(CH2CH2O) m -R4, -(CH(CH3)CH2O) n -R4, or -(CH2CH2OCH(CH3)CH2O) y -R4, m, n, and y are independently integers ranging from 7 to 100; R4 is hydrogen or methyl; R5 is hydrogen, methyl, or -CH2COOH; R6 is -OH, -OCH2OH, -OCH2CH2OH, -OCH2CH2CH2OH, -OCH2CH2CH2OH, -OCH2CH(CH3)CH2OH, -OCH2CH2CH2CH2OH, -NHR7, a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising a period of at least 2 hours beginning after all of the above amounts of A, B, C, D and E have been introduced into the mixing chamber; The method further relates to a process wherein the single slump flow class is S3, S4 or S5.
[0096] The components of the wet concrete or wet mortar compositions classified in one of the slump flow classes S3, S4 and S5 according to standard NF EN 206, to which the method according to the invention is applied, have the same characteristics apart from those described above in the section "Ready-mixed concrete or mortar, or precast concrete compositions".
[0097] In particular, in the process according to the invention, the water-reducible polymer (E) is anionic, cationic or zwitterionic.
[0098] In particular, in the method according to the invention, the mass ratio C / B of said alkali sulfate activator (C) to the binder composition (B) is comprised between 0.001 and 0.15.
[0099] In particular, in the method according to the invention, the auxiliary cementitious material (b3) is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, or mixtures thereof, and / or the filler material (b4) is selected from the group consisting of crushed limestone, crushed dolomite, marble flour, silica sand, recycled concrete fine aggregate, or mixtures thereof. EXAMPLES
[0100] Concrete composition and testing: The main parameters of cast concrete are listed below: Granular framework optimized with five aggregate size ranges (Dmax=20mm) 350kg / m 3 CEM III / B (70% GGBS+30% CEM I) Water to binder ratio is 0.45 (to account for water absorption from aggregates) Na2SO4 is added as a hardening accelerator at 1.5% by weight of the binder content. The concrete was cast and cured according to standard NF EN 12390-2.
[0101] Slump tests were realized with an Abrams cone according to standard NF EN 12350-2. Tests were performed every 30 minutes and the slump was monitored for up to 1 hour and 30 minutes. Before each new test, the concrete was mixed for 30 seconds.
[0102] The compression strength test was carried out using a cubic mold (10 x 10 x 10 cm 3 ) and was realized in accordance with standard NF EN 12390-3. The compressive strength results were the average values obtained by crushing three cube samples per test age.
[0103] Mortar composition and testing: The aggregate used in the mortar preparation was standardized quartz sand with particle size 0-2 mm according to NF EN 196-1. The mass of the binder (cement + GGBS) was kept constant at 550 g. The granule-to-sand ratio (ratio of granules to sand) and the water-to-binder ratio (ratio of water to binder) were set at 2.45 and 0.35, respectively. The mixing procedure was according to NF EN 196-1.
[0104] Comparative slump tests were carried out with cones, all proportions corresponding to half of the Abrams cone according to NF EN 12350-2. For the concrete procedure, the mortar was placed in the cone in three identical layers. Each layer was compacted with a compaction bar with 25 strokes. The slump test was repeated with the same mortar every 30 minutes to evaluate its open time. Before each new slump test, the mortar was mixed at high speed for 30 seconds with a planetary mixer according to NF EN 196-1. As soon as the slump test was finished, the mortar was reintroduced into its mixing bowl and covered with a damp cloth.
[0105] For compressive strength testing, 4 x 4 x 16 cm 3 The mortar was cast in a mold of 40×40 mm. 2 A press with a contact surface of 2.4 kN / s was used with a loading rate of 2.4 kN / s. Results were the average of three values.
[0106] Example of a test using HPEG
[0107] Example 1 (Improved initial flow) - 0 and 1% Na 2 SO 4 CEN Mortar Test (w / b 0.4) composition: 450g binder containing 45% GGBS-35% OPC-20% limestone filler CEN sand 1350g 0-1% Na2SO4 Water-reducing polymer: 0.06 to 0.45% of the binder.
[0108] The HPEG behaviour was tested in a composition similar to the new CEM VI formula (as set out in EN 197-5) and compared to a conventional PCE ViscoCrete® Tempo 12 manufactured by Sika®.
[0109] The HPEG products are more efficient at dispersing systems (requiring less dispersion for the same rheological properties).
[0110] HPEG did not affect early age compressive strength at this percentage, but ViscoCrete® Tempo 12 had a detrimental effect as shown in FIG.
[0111] [Table 1]
[0112] Example 2 (Improved initial liquidity) Testing of binders in concrete with normal PCE using 70% GGBS and 30% CEM I as binder by using sodium sulfate activation for initial fluidity (Concrete S4 class). In the following example, sodium sulfate + HPEG instead of ordinary PCE is used.
[0113] Composition for concrete S4 slump flow: 70% GGBS-30% OPC binder 350kg / m 3 PSD / D max = 22.5mm optimized aggregate W / B≦0.45 1.5% Na2SO4 Water-reducing polymer: PCE Viscocrete® Tempo 12 or HPEG RB1050® manufactured by Marla® (additive amount to binder)
[0114] Figure 2 shows the results of rheological measurements performed with an Abrams cone for a precast application. The room temperature was higher than standard laboratory conditions (25-26 °C) to simulate deteriorated conditions for a precast application.
[0115] By adding PCE type normal water-reducing polymers such as Sika Viscocrete® Tempo 12 to concrete applications, it is not possible to obtain an initial fluidity of 20±1 cm corresponding to S4 concrete class, despite very high dosages for normal applications (1.6% relative to the binder). This is due to the addition of sodium sulfate as GGBS activator, which strongly deteriorates the initial fluidity.
[0116] The Abrams cone measurement for the ViscoCrete® Tempo 12 composition was 16.5 cm at the first measurement (t0+9 min), then the concrete was held for about 30 min, after which it hardened strongly from 60 min onwards. In fact, this water-reducible polymer is not particularly robust against alkali sulfates and does not allow a satisfactory slump, either initially or in terms of open time.
[0117] The addition of HPEG type water-reducing polymers such as RB 1050® at a very low loading of 0.5% to the binder resulted in a slump of 24.5 cm at T0+7 min. Thus, the HPEG-based RB 1050® water-reducing polymer is promising for reducing the viscosity of systems containing sodium sulfate as an activator.
[0118] As shown in FIG. 3, the addition of HPEG did not have any adverse effect on the mechanical strength (compressive strength) of the concrete specimens measured at 2 and 28 days.
[0119] Example 3 - Testing of mortar for long open time applications such as RMX applications Composition (T=20℃): Binder containing 70% GGBS-30% OPC = 550g Sand EN 196-1 = 1350g W / B = 0.35 1.5% Na2SO4 Water-reducing polymers: See below
[0120] Several water-reducing polymers were tested, and even combinations of the two, in fact it is quite common in concrete applications to combine two water-reducing polymers, one for initial flow and one for open time.
[0121] Figure 4 compares the rheology results with the following water-reducing polymers: 0.25% RB 1050® (HPEG type for initial liquidity) 0.60% ViscoCrete® Tempo 12 (PCE type for initial flow) 0.20% RB 1050® + 0.10% PC 1901® manufactured by Marla (HPEG type for longer workability) 0.15% RB 1050® + 0.20% PC 1901® 0.15% RB 1050® + 0.30% TempoFlow® 464 manufactured by Sika® (PCE type for longer workability)
[0122] The mortar with ViscoCrete® Tempo 12 is the mortar with the least decrease in spread over 2 hours, but the average spread obtained is too low for the corresponding S4 type flowable concrete.
[0123] The initially most fluid mortar is the one mixed with 0.25% RB 1050® alone. A slight seepage appears early on, so the dosage can be further reduced, already much lower than ViscoCrete® Tempo 12. On the other hand, this mixture does not provide good rheological maintenance, with a strong drop in the spreading value between 30 and 60 minutes, from 350 mm to 270 mm, then at 90 minutes to 150 mm.
[0124] As shown in Figure 4, the combination of RB 1050® and PC 1901® allows to have good initial fluidity and improves the open time (open circle curve). The mortar containing the combination of PC 1901® and RB 1050® shows a lower initial spreading than the mortar containing RB 1050 but not PC 1901, but the spreading decreases less over time and gives a longer open time (open circle vs. closed circle).
[0125] The combination of 0.15% RB 1050® + 0.30% Tempoflow® 464 also failed to achieve sustained spreading, confirming that the combination is not effective when alkali sulfates are used.
[0126] A second series of tests was conducted by focusing on a combination of several HPEG Marla water-reducible polymers: RB1050® for initial flow and PC 1901® for maintenance.
[0127] Figure 5 shows the Abrams mini-cones for mortars based on a binder containing 70% GGBS-30% OPC, with 1.5% Na2SO4 added, and various combinations of water-reducing polymers as follows: 0.20% RB 1050® + 0.10% PC 1901® (first series of tests - Figure 4) 0.20% RB 1050 (registered trademark) + 0.15% PC 1901 (registered trademark) 0.20% RB 1050 (registered trademark) + 0.20% PC 1901 (registered trademark)
[0128] It was observed that with the same amount of RB 1050®, an increase in the amount of PC 1901® indeed made it possible to maintain good rheology of these mortars over a period of 2 hours.
[0129] Example 4 – HPEG Efficacy in Sodium Sulfate Activated Paste composition: Pastes were prepared using binders based on the following: 25% GGBS 15% CEM I 30% SCM pozzolan 30% Dual Filler: 20% Durcal® 65, 10% Betocarb® F-SL
[0130] The water to powder ratio used was 0.40, chosen so that any difference in rheology would appear large and would result in a worse rheological condition. Sodium sulfate = 0% or 2% bwp (weight percentage relative to the binder) Water-reducing polymers: HPEG RB-1050® manufactured by Sika and PCE Sika Viskocrete 125 P (powder form)
[0131] All pastes were subjected to the same testing procedure.
[0132] The powders were homogenized at 200 rpm for 30 seconds before the addition of water and water-reducing polymer. After these additions, the paste was mixed at 150 rpm for 30 seconds and at 650 rpm for 1 minute. The mixing rheology procedure was used to follow the evolution of the rheological behavior. Once in the rheometer, the paste was mixed at a shear rate of 0.1 s -1 100 seconds from -1 The flow sweeps were cycled three times, with the flow rate varying from 0.1 s to 100 s. Between each flow sweep, a 20 min small amplitude oscillatory test was performed as a non-destructive method. In the case presented here, the apparent viscosity was measured as a function of shear rate and 0.1 s. -1 The shear rate is measured between the last two points of yield stress at 100 MPa. The entire test lasts approximately 60 min.
[0133] With regard to yield stress (FIG. 6), HPEG RB-1050® showed less change in yield stress between time zero and 60 minutes due to the presence of sodium sulfate.
Claims
1. A wet ready-mix concrete or mortar composition, or a wet precast concrete composition, in particular for building and civil engineering construction, comprising at least one aggregate (A), a binder composition (B), at least one alkali and / or alkaline earth sulfate activator (C), water (D) and at least one water-reducing polymer (E), wherein said binder composition (B) is (b5) ground granulated blast furnace slag (GGBS); (b6) optionally at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b7) optionally, one or more auxiliary cementitious materials; and (b8) optionally, one or more filler materials; Including, The wet ready-mix concrete or mortar composition or the wet precast concrete composition is classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, and The water-reducible polymer (E) comprises the following monomer units: - Unit A 【Chemistry 1】 - Unit B 【Chemistry 2】 - Unit C 【Chemistry 3】 - Unit D 【Chemistry 4】 [In the formula, 【Chemistry 5】 represents the binding site of the monomer unit, the amount of monomer unit A is 0-40 mol %; the amount of monomer unit B is 25 to 95 mol %; the amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R 1 and R 2 are independently hydrogen or methyl; Z 1 is a bond, methyl, or ethyl; Z 2 is a bond, -CH 2 CH 2 O-, -CH 2 CH 2 OCH 2 CH 2 O- or -CH 2 CH 2 CH 2 CH 2 O-, R 3 is -(CH 2 CH 2 O) m -R 4 , -(CH(CH 3 ) CH 2 O) n -R 4 , or -(CH 2 CH 2 OCH (CH 3 ) CH 2 O) y -R 4 and m, n, and y are independently integers ranging from 7 to 100; R 4 is hydrogen, methyl, R 5 is hydrogen, methyl, or -CH 2 COOH, R 6 is -OH, -OCH 2 OH, -OCH 2 CH 2 OH, -OCH 2 CH 2 CH 2 OH, -OCH 2 CH (CH 3 ) CH 2 OH, -OCH 2 CH 2 CH 2 CH 2 OH, -NHR 7 , a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R 7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising A wet ready-mix concrete or mortar composition, or a wet precast concrete composition.
2. 2. The wet ready mix concrete or mortar composition of claim 1, wherein the wet concrete or wet industrial mortar composition remains classified in the same slump flow class for at least 2 hours after adding all of the amount of water (D).
3. 3. The wet ready-mix concrete or mortar composition, or the wet precast concrete composition, according to claim 1 or 2, wherein the water-reducing polymer is anionic, cationic, or zwitterionic.
4. The wet ready-mix concrete or mortar composition, or the wet precast concrete composition, according to any one of claims 1 to 3, wherein the mass ratio C / B of the alkali sulfate activator (C) to the binder composition (B) is comprised between 0.001 and 0.
15.
5. 5. The wet ready-mix concrete or mortar composition or wet precast concrete composition according to any one of claims 1 to 4, wherein the auxiliary cementitious material (b3) is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, or mixtures thereof, and / or the filler material (b4) is selected from the group consisting of crushed limestone, crushed dolomite, marble flour, silica sand, recycled fine concrete aggregate, or mixtures thereof.
6. 6. Hardened concrete or mortar obtained from a wet ready-mix concrete or mortar composition or a wet precast concrete composition according to any one of claims 1 to 5.
7. A method for producing a wet concrete or wet mortar composition classified in one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, comprising the steps of: At least one aggregate (A), Binder composition (B), at least one alkali sulfate activator (C); Water (D), and At least one water-reducible polymer (E) into a mixing chamber, The binder composition (B) is (b5) ground granulated blast furnace slag (GGBS); (b6) optionally at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b7) optionally, one or more auxiliary cementitious materials; and (b8) optionally, one or more filler materials; Including, The water-reducible polymer (E) comprises the following monomer units: - Unit A 【Chemistry 6】 - Unit B 【Chemistry 7】 - Unit C 【Chemistry 8】 - Unit D 【Chemistry 9】 [In the formula, 【Chemistry 10】 represents the binding site of the monomer unit, the amount of monomer unit A is 0-40 mol %; the amount of monomer unit B is 25 to 95 mol %; the amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R 1 and R 2 are independently hydrogen or methyl; Z 1 is a bond, methyl, or ethyl; Z 2 is a bond, -CH 2 CH 2 O-, -CH 2 CH 2 OCH 2 CH 2 O- or -CH 2 CH 2 CH 2 CH 2 O-, R 3 is -(CH 2 CH 2 O) m -R 4 , -(CH(CH 3 ) CH 2 O) n -R 4 , or -(CH 2 CH 2 OCH (CH 3 ) CH 2 O) y -R 4 and m, n, and y are independently integers ranging from 7 to 100; R 4 is hydrogen, methyl, R 5 is hydrogen, methyl, or -CH 2 COOH, R 6 is -OH, -OCH 2 OH, -OCH 2 CH 2 OH, -OCH 2 CH 2 CH 2 OH, -OCH 2 CH (CH 3 ) CH 2 OH, -OCH 2 CH 2 CH 2 CH 2 OH, -NHR 7 , a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R 7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising The method according to claim 1, wherein the wet concrete or wet industrial mortar composition remains classified in the same slump flow class for at least 2 hours after introducing all of the above amounts of A, B, C, D and E into the mixing chamber.
8. The method of claim 7, wherein the water-reducible polymer is anionic, cationic, or zwitterionic.
9. 9. The method according to claim 7 or 8, wherein the weight ratio C / B of the alkali sulfate activator (C) to the binder composition (B) is comprised between 0.001 and 0.
15.
10. 10. The method according to any one of claims 7 to 9, wherein the auxiliary cementitious material (b3) is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, or mixtures thereof, and / or the filler material (b4) is selected from the group consisting of crushed limestone, crushed dolomite, marble flour, silica sand, recycled concrete fine aggregate, or mixtures thereof.
11. A method for maintaining a wet concrete composition or a wet industrial mortar composition in a single slump flow class according to standard NF EN 206 for at least 2 hours, said composition comprising at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D) and at least one water-reducing polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS); (b2) optionally at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) optionally, one or more filler materials; Including, The water-reducible polymer (E) comprises the following monomer units: - Unit A 【Chemistry 11】 - Unit B 【Chemistry 12】 - Unit C 【Chemistry 13】 - Unit D 【Chemistry 14】 [In the formula, 【Chemistry 15】 represents the binding site of the monomer unit, the amount of monomer unit A is 0-40 mol %; the amount of monomer unit B is 25 to 95 mol %; the amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R 1 and R 2 are independently hydrogen or methyl; Z 1 is a bond, methyl, or ethyl; Z 2 is a bond, -CH 2 CH 2 O-, -CH 2 CH 2 OCH 2 CH 2 O- or -CH 2 CH 2 CH 2 CH 2 O-, R 3 is -(CH 2 CH 2 O) m -R 4 , -(CH(CH 3 ) CH 2 O) n -R 4 , or -(CH 2 CH 2 OCH (CH 3 ) CH 2 O) y -R 4 and m, n, and y are independently integers ranging from 7 to 100; R 4 is hydrogen, methyl, R 5 is hydrogen, methyl, or -CH 2 COOH, R 6 is -OH, -OCH 2 OH, -OCH 2 CH 2 OH, -OCH 2 CH 2 CH 2 OH, -OCH 2 CH (CH 3 ) CH 2 OH, -OCH 2 CH 2 CH 2 CH 2 OH, -NHR 7 , a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R 7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. is a copolymer comprising said at least two hour period beginning after all of the above amounts of A, B, C, D and E have been introduced into the mixing chamber; and The method, wherein the single slump flow class is S3, S4, or S5.
12. The method of claim 11 , wherein the water-reducible polymer is anionic, cationic, or zwitterionic.
13. 13. The method according to claim 11 or 12, wherein the weight ratio C / B of the alkali sulfate activator (C) to the binder composition (B) is comprised between 0.001 and 0.
15.
14. 14. The method according to any one of claims 11 to 13, wherein the auxiliary cementitious material (b3) is selected from the group consisting of fly ash, mechanically or thermally activated clay, silica fume, natural pozzolanic materials, rice husk ash, activated recycled concrete fine aggregate, or mixtures thereof, and / or the filler material (b4) is selected from the group consisting of crushed limestone, crushed dolomite, marble flour, silica sand, recycled concrete fine aggregate, or mixtures thereof.
15. 1. A method for imparting to a hardened low carbon GGBS containing binder based concrete or mortar composition an early age compressive strength value comparable to that of a hardened 100% OPC binder based concrete or mortar composition, comprising the steps of: A wet precursor P1 of a concrete or mortar composition based on a low-carbon GGBS-containing binder comprises at least one aggregate (A), a binder composition (B), at least one alkali sulfate activator (C), water (D), and at least one water-reducible polymer (E), The binder composition (B) is (b1) Ground Granulated Blast Furnace Slag (GGBS); (b2) optionally at least one hydraulic binder other than GGBS in accordance with standards EN 197-1 and EN 197-5; (b3) optionally, one or more auxiliary cementitious materials; and (b4) optionally, one or more filler materials; Including, said wet precursor P1 being classified into one of the slump flow classes S3, S4 and S5 according to the standard NF EN 206, The wet P1 remains classified into the same slump flow class for at least 2 hours after the above amounts of components A, B, C, D and E are all introduced into the mixing chamber; a wet precursor P2 of a 100% OPC binder based concrete or mortar composition comprising the same components (A), (D), and (E) as P1, wherein (A), 100% OPC, (D), and (E) are in the same concentrations as (A), (B), (D), and (E) in P1, and wherein the C / 100% OPC binder ratio is the same as the C / B ratio in P1; The method comprises providing a monomer unit comprising: - Unit A 【Chemistry 16】 - Unit B 【Chemistry 17】 - Unit C 【Chemistry 18】 - Unit D 【Chemistry 19】 [In the formula, 【Chemistry 20】 represents the binding site of the monomer unit, the amount of monomer unit A is 0-40 mol %; the amount of monomer unit B is 25 to 95 mol %; the amount of monomer unit C is 5 to 50 mol %; the amount of monomer unit D is 0-25 mol %; R 1 and R 2 are independently hydrogen or methyl; Z 1 is a bond, methyl, or ethyl; Z 2 is a bond, -CH 2 CH 2 O-, -CH 2 CH 2 OCH 2 CH 2 O- or -CH 2 CH 2 CH 2 CH 2 O-, R 3 is -(CH 2 CH 2 O) m -R 4 , -(CH(CH 3 ) CH 2 O) n -R 4 , or -(CH 2 CH 2 OCH (CH 3 ) CH 2 O) y -R 4 and m, n, and y are independently integers ranging from 7 to 100; R 4 is hydrogen, methyl, R 5 is hydrogen, methyl, or -CH 2 COOH, R 6 is -OH, -OCH 2 OH, -OCH 2 CH 2 OH, -OCH 2 CH 2 CH 2 OH, -OCH 2 CH (CH 3 ) CH 2 OH, -OCH 2 CH 2 CH 2 CH 2 OH, -NHR 7 , a group having a phosphate functional group, a group having a phosphonate functional group, or a group having a sulfonate functional group; R 7 is a saturated or unsaturated, linear or branched chain containing 2 to 12 carbon atoms and eventually one or more heteroatoms, preferably O, N or S. using a water-reducible polymer (E) which is a copolymer comprising method.
Citation Information
Patent Citations
Binder composition comprising a water reducing polymer and a chaotrope ion and use thereof for improving superplasticizer efficiency in alkali-activated cements
WO2021204384A1